Science discovery files : 10 forgotten stories of incredible scientists - Lincoln, Diane (Singapore : WS Education, 2022)
This book is a breath of fresh air and a valuable resource for the younger set of teens, it discusses about the 10 forgotten stories of incredible scientists.
Keywords: Study and teaching (Elementary). -